G221(P) A change in the approach to the management of sore throat in children. (25th October 2020) - Duthie, L; Doan, L; Griffiths, S; Munthali, P
Abstract : Aims: Sore throat and fever is a common reason for children to present acutely to the Emergency Department. Despite mainly being a self-limiting illness, antibiotics are often prescribed despite limited evidence of benefit. Previous practice had been to use bacterial throat swabs to identify children who require antibiotic treatment. However, recent NICE guidelines have promoted a score based approach to treatment (FeverPain or Centor) in order to limit antibiotic use and reduce resistance. This approach is still not followed uniformly, and in some units bacterial throat swabs are being taken routinely to guide treatment. Our aim was to identify whether the use of bacterial throat swabs in our unit was leading to over-prescribing of antibiotics and the medicalisation of a primarily self-resolving illness Methods: We retrospectively reviewed the use of antibiotics for sore throat on 60 patients who had throat swabs taken between October and November 2018. Swab results were retrieved from the microbiology information system and FeverPain (FPS) score was calculated from clinical notes. Results: Clinical scores were not documented for any patients. 38 children (63%) were prescribed antibiotics, 20 (53%) of which were prescribed for 5 days and then discontinued after a negative throat swab result was received. Only 5 (8%) patients were confirmed as having a Group A Streptococcus on their throat swab, 4 of whom had been initiated on antibiotics. Of the 38 children given antibiotics, 18 (47%) met the FPS criteria for treatment. (score 4 or 5). A further 6 out of the 11 children who were not prescribed antibiotics, also met the criteria. Conclusions: Less than half of those children who were treated with antibiotics would have required treatment if the FeverPain score was used. Implementing a score based approach would have reduced the overall antibiotic prescribing from 63% to 40%. Not only would this reduce unnecessary antibiotic use and the costs associated with performing throat swabs but would also be more in line with practice in primary care, emphasising the self-limiting nature of the illness and the ability to manage at home.